Peran Kepemimpinan Suatu Institusi dalam Mengakselerasi Penanganan Korupsi di Era Digitalisasi 5.0 dan Sosial Media dengan Kepemimpinan Manajemen Pendidikan Islam - Kurnia, Dian Salshabila; Soeratin, Harry Z. (Lembaga Yasin AlSys, 2023)
This study aims to explore the role of leadership in an institution in accelerating the handling of corruption in the era of digitalization 5.0 and social media, with a focus on Islamic education management leadership. In the increasingly advanced digitalization era, corruption has become a serious threat that affects various sectors, including education. The leadership of Islamic educational institutions has an important responsibility in leading change and creating an environment free from corruption. In this research, we will analyze effective leadership strategies, such as building a culture of transparency and accountability, increasing digital and media literacy, and harnessing the power of social media in fighting corruption. Through this approach, leadership in the management of Islamic education can play a key role in accelerating efforts to deal with corruption in the era of digitalization 5.0 and social media.